2019
DOI: 10.1007/s00415-019-09409-7
|View full text |Cite
|
Sign up to set email alerts
|

A bedside application-based assessment of spatial orientation and memory: approaches and lessons learned

Abstract: Spatial orientation and memory deficits are an often overlooked and potentially powerful early marker for pathological cognitive decline. Pen-and-paper tests for spatial abilities often do not coincide with actual navigational performance due to differences in spatial perspective and scale. Mobile devices are becoming increasingly useful in a clinical setting, for patient monitoring, clinical decision-making, and information management. The same devices have positional information that may be useful for a scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The authors stated the ability to find one's way that involved basic perceptual and memory-related processes are seen as a complex construct due to the multisensory process in which information needs to be adjusted over space and time (Wolbers and Hegarty 2010). The correlation between the spatial orientation and memory is shown in a study in which deficits of them are known as an early marker for pathological cognitive declines (Flanagin et al 2019). Therefore, different tests were used to analyze spatial memory by letting the participants conduct a test that required them to memorize the order of objects on a map and to reconstruct it from memory (Lehnung et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors stated the ability to find one's way that involved basic perceptual and memory-related processes are seen as a complex construct due to the multisensory process in which information needs to be adjusted over space and time (Wolbers and Hegarty 2010). The correlation between the spatial orientation and memory is shown in a study in which deficits of them are known as an early marker for pathological cognitive declines (Flanagin et al 2019). Therefore, different tests were used to analyze spatial memory by letting the participants conduct a test that required them to memorize the order of objects on a map and to reconstruct it from memory (Lehnung et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The authors emphasized the meaning of both reference systems but also referred to studies that crystallized the egocentric reference system as the dominant role to specify objects' locations (Battaglia-Mayer et al 2003;Klatzky 1998). For measuring environmental spatial abilities, pointing is a commonly used method that can be varied to examine different aspects of spatial ability (Flanagin et al 2019;Kimura et al 2017). Kimura et al (2017) found out that participants could reorient by using either the geometry of the room or the implemented features (objects), whereas feature-based cues seem to have more impact on spatial ability skills in virtual environments.…”
Section: Introductionmentioning
confidence: 99%
“…Functional MRI (fMRI) based studies are mostly possible in 2D paradigms and hard to achieve in immersive VR set-ups. Examples of real space spatial orientation and navigation testing by (D) pointing experiments to a known position in vista space (Flanagin et al, 2019) and (E) navigation in large-scale environments. Navigation strategy and visual exploration patterns are recorded by a head-mounted eye-tracking system and are analyzed post hoc in navigograms.…”
Section: Navigation Testing In Vr and Real Space-a Critical Discussionmentioning
confidence: 99%
“…These basic activities qualify for a quick clinical bedside test of a patient’s ability to perform spatial navigation and orientation. A first prototype of our handheld pointing device using the inbuilt sensors of an Apple iPhone® showed promising results [ 6 ]. While this approach did show the principal feasibility of harnessing the sensor output from a modern smartphone for neuroscientific navigation testing, it relied on GPS and compass information, therefore, suffering from limited applicability indoors (as positioning via GPS does require an uninterrupted line-of-sight towards the satellites orbiting earth) and proneness to errors in the presence of magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…In the following, we will first discuss structural and functional aspects of spatial orientation, the specific meaning of pointing as a fundamental element of interaction with the environment and its fallibility when using pointing as a quantitative measure for spatial orientation. Then, we will analyze the shortcomings of the methods and the pointing device used in our initial description for a bedside application-based assessment [ 6 ]. Finally, we will propose a further developed pointing device with a modified standardized test paradigm and report the preliminary data of a pilot experiment in healthy participants.…”
Section: Introductionmentioning
confidence: 99%